Unexpected Supremacy of Non‐Dysprosium Single‐Ion Magnets within a Series of Isomorphic Lanthanide Cyanocobaltate(III) Complexes - Babeshkin, Konstantin A.; Gavrikov, Andrey V.; Petrosyants, Svetlana P.; Ilyukhin, Andrey B.; Belova, Ekaterina V.; Efimov, Nikolay N. (European journal of inorganic chemistry, 2020)
Slow relaxation of magnetization has been studied for a series of stable isomorphic 3D‐polynuclear Ln‐Co complexes comprising hexadentate [Co(CN)6]3– linkers, namely {[Ln(H2O)2][Co(CN)6]·2H2O}n where Ln = Tb (1), Dy (2), Er (3) and Yb (4). While 1 and 4 behave as field‐induced single‐ion magnets (SIMs), compounds 2 and 3 undergo rapid demagnetization even under magnetic fields up to 5000 Oe. The effective anisotropic energy barrier of 4 was estimated as 63 K (5000 Oe) which, to the best of our knowledge, is the highest value among Yb‐based SIMs. The obtained data are discussed in scope of the configuration of the Ln environment, i.e. accounting its composition and geometry as well as mutual arrangement of chemically unequal donating centers. Thus, the studied series of complexes represents very rare case when SIM performance of non‐dysprosium complexes far surpasses that of isomorphic Dy derivative. A study of Ln cyanocobaltates(III) as single‐ion magnets (SIMs) revealed drastic supremacy of Tb and Yb derivatives over Dy one which is still a rare case among a particular series of isomorphic complexes. Moreover, Δeff/kB value for Yb derivative is the highest one among both mononuclear SIMs and polynuclear single‐molecule magnets (SMMs) formed by that lanthanide.